THE EVOLUTION OF THE GRAPHICAL USER INTERFACE: FROM SKEUOMORPHISM TO MATERIAL DESIGN - Gatsou, Chrysoula; Farrington, John Steven (Design/Arts/Culture, 2022)
Graphical user interfaces are an evolution of the command line user interfaces of the past. Graphical user interfaces allow users to interact with devices while using the metaphor of a desktop surface. As technology evolved, user interfaces became more elaborate, going through various design phases such as skeuomorphism and modern, flat design. User interfaces have become more simplified and use fewer non-essential design elements. This also allows for easier cross-platform development. Due to the widespread adoption of technology, clear user interfaces that put usability first, have and will become very important in the years to come. We present the very beginnings of the GUI, its evolution through the years and finally focus on modern graphical user interfaces while also going over various problems